MODERN APPROACH TO THE TREATMENT AND PREVENTION OF ABDOMINAL CONNECTION DISEASE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The article examines the treatment of various clinical forms of peritoneal adhesive disease in 114 children. Based on this, a modern approach to surgical and conservative treatment methods, the clinical course, and the effectiveness of the conservative measures taken depending on the forms of the disease are determined. To achieve the set goal, treatment measures are aimed at significantly reducing the number of unjustified operations and complications, and decreasing mortality. In clinical practice, the prevention of peritoneal adhesive disease, the use of complex treatment methods, allows for a reduction in the recurrence of adhesive disease and a decrease in its complications.